Hip and Trunk Variables in University Students with and without Recurrent Low Back Pain - BJ Lehecka; Jordin Burleson; Paige Diederich; Morgan Salem; Rachel Schoonover; Jason Tejano (North American Sports Medicine Institute, 2024)
# Background Low back pain (LBP) is a leading cause of disability. Recurrent low back pain (rLBP) is defined as two or more episodes of LBP in a 12-month period, each lasting more than 24 hours and separated by at least one pain-free month. Many studies have shown that hip and trunk variables have an influence on LBP. However, most of these are studies of participants with acute or chronic LBP rather than rLBP. # Purpose To examine the difference between hip and trunk variables of university students with and without rLBP. # Study Design Cross-Sectional # Methods Participants with and without rLBP between 18 and 35 years of age not currently undergoing clinical orthopedic care were recruited for this cross-sectional study. Bilateral hip range of motion (ROM) and trunk ROM were measured with a goniometer or measuring tape (hip motions in all planes along with trunk flexion, extension, and lateral flexion). Strength of the hip extensors, abductors, and external rotators was measured using a handheld dynamometer, and a single-leg bridge endurance test was performed to assess differences and correlations between outcomes. # Results Twenty-six subjects aged 18 to 35 years with rLBP (n=10) and without rLBP (n=16) participated. Statistically significant differences between the two groups were found for right and left hip flexion (p = 0.029 and 0.039, respectively), right hip adduction (p = 0.043), and right hip extension (p = 0.021). No significant differences were found between groups for strength, endurance, or other ROM measures. # Conclusion The findings of this study show statistically significant although clinically non-meaningful differences in hip flexion, extension, and adduction ROM in the rLBP group compared to the control group. This lack of clinically meaningful difference may be relevant to testing procedures and treatment of patients or athletes with rLBP. This study also suggests that hip strength and endurance may not play a major role in the development or treatment of rLBP.\ \ **Level of Evidence:** 3